Macrophytes in Inland Waters From Knowledge to Management - Troia, Angelo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue includes 10 contributions centered on aquatic plants (and charophytes) in inland waters, with different approaches: floristic contributions and new reports of interesting or rare species, ecological studies on the use of macrophytes to characterize rivers and ponds, a genetic study to assess the diversity of an aquatic species within and among populations, the importance of herbaria in the study of a species, and finally a couple of interesting reviews on the use of hydrophytes and charophytes in wetland restoration.